PENGARUH KUALITAS PRODUK DAN HARGA PRODUK TERHADAP KEPUASAN PELANGGAN IMPLIKASI PADA LOYALITAS PELANGGAN PENGGUNA ANDROID SAMSUNG DI MALL KALIBATA - Nursukmana Triwahyudi dan Sumarni (Fakultas Ekonomi Universitas Borobudur, 2017)
The data used in this study is the primary data obtained from the results of questionnaires and interviews on Samsung Android users in Mall Kalibata. The method of data processing using path analysis method with the help of SPSS analysis 22.The results showed that method I: Directly variable Product Quality and Product Price significantly influence Customer Satisfaction. Method II: Directly variable of Product Price, Product Quality, and Customer Satisfaction have a significant effect on Customer Loyalty. Indirectly Product Quality and Product Price influence on Customer Loyalty through Customer Satisfaction variable. Keywords: Product Quality, Product Price, Customer Satisfaction, Customer loyalty